A registration-and-fixation approach with handpiece adjustment for dynamic navigation in dental implant surgery. Issue 9 (September 2022) - Wu, Bin-Zhang; Sun, Feng
Abstract: The deviations between the preoperative (planned) and postoperative (actual) positions of dental implants have always been of a major concern in dental implant surgery. Dynamic computer-aided implant surgery (dCAIS) systems have been used to achieve optimal implant positioning. The method of registration is indeed an important factor that affects the implanting accuracy. Here, we propose a fast and concise registration method using a registration-and-fixation device as well as an adjustable handpiece for dynamic navigation in dental implant surgery. To the best of our knowledge, our work is the first study of such a registration method for dynamic navigation in a dental implant system. Abstract : Dynamic navigation; Registration method; registration-and-fixation approach; Accuracy; Implant surgery